Нові аспекти соціально – економічного розвитку цифрового суспільства - Загоруйко, А. (ХНУРЕ, 2023)
The article examines the economic problems of the information society. Human society in the 21st century faced new economic realities. The information world is gradually becoming increasingly digital, and traditional forms of economic effects, competition, and antitrust behavior are changing accordingly. New forms of monopolization and market power are clearly visible in the modern economy. The state faced the problem of regulating the economy taking into account the new digital realities. The antimonopoly legislation of many countries makes it a difficult task to ensure that the behavior of economic companies meets the demands and needs of society.